Peran Para Pihak dalam Rehabilitasi Hutan dan Lahandi Kecamatan Tapung Kabupaten Kampar: The Role of Stakeholders in Forest and Land Rehabilitation in Tapung Sub District, Kampar District - Qomar, Nurul; Mardianti, Gusdina; Oktorini, Yossi (Jurnal Ilmu Ilmu Kehutanan, 2025)
Forest degradation in river basins can cause soil erosion and landslides in upstream areas, as well as flooding in downstream areas, thereby expanding critical land areas. To reduce the extent of critical land, comprehensive forest and land rehabilitation efforts must be undertaken with the involvement of multiple stakeholders. Activities conducted in Tapung Sub-district, Kampar Regency include reforestation of the Imbo Putui Traditional Forest area, seedling planting along the Tapung River, roadside planting, school ground plantations, and similar initiatives. This research aims to identify the roles of various stakeholders in forest and land rehabilitation (RHL) activities in Tapung Sub-district, Kampar Regency. This study employs qualitative methods, collecting data through observation, in-depth interviews, and documentation studies to obtain both primary and secondary data. Data analysis was conducted using descriptive qualitative techniques. The research findings reveal that multiple stakeholders are involved in forest and land rehabilitation activities. Forest farmer groups play an implementation role in community nursery and village nursery programs to provide seedlings required for forest and land rehabilitation activities, with funding facilitated by BPDASHL Indragiri Rokan, which serves as the program initiator and supervisor. DLHK Riau Province and KPH Suligi Batu Gajah function as coordinators and facilitators in seedling procurement and distribution to communities. KODIM 0313/KPR serves as protector and activity supervisor. Community-based forestry extension officers act as catalysts, mediators, motivators, and educators within the community. Private companies also contribute as financial and material supporters through corporate social responsibility program implementation.